The incidence of outpatient care within 24 months from SARS-CoV-2 infection in the general population: a multicenter population-based cohort study - Federico Banchelli; Carlo Gagliotti; Angela De Paoli; Rossella Buttazzi; Elena Narne; Enrico Ricchizzi; Silvia Pierobon; Ugo Fedeli; Gisella Pitter; Elisa Fabbri; Michele Tonon; Elisa Gentilotti; et al. (BMC Infectious Diseases)
Abstract Background The long-term effects of COVID-19, which can vary significantly in type and timing, are considered relevant and impacting on the well-being of individuals. The present study aims to assess the incidence of outpatient care in the post-acute phase of SARS-CoV-2 infection in two Italian regions. Methods The study has a multicentre, population-based, pre-post, repeated measures design to compare the incidence rate of access to outpatient visits and diagnostics before and after SARS-CoV-2 infection, considering a follow-up of 24 months. The study made use of previously recorded large-scale healthcare data available in the administrative databases of the Emilia-Romagna (E-R) and Veneto regions. Analyses were carried out separately in the two regions and results were pooled using random effects meta-analysis. Results There were 27,140 subjects in E-R and 22,876 in Veneto who were included in the analysis. The pooled outputs showed an increase in rates of outpatient visits and diagnostics starting from month 2 after SARS-CoV-2 infection (IRR = 1.68, 95% CI = 1.56–1.81) with a peak at month 4 (IRR = 2.05, 95% CI = 1.95–2.15); the increase continued with reduced intensity up to month 15. Stratified analysis revealed that subjects with severe acute COVID-19 had a higher increase in rates (up to IRR = 3.96, 95% CI = 2.89–5.44), as well as patients with no comorbidities (up to IRR = 2.71, 95% CI = 2.60–2.83). Conclusion Long-term effects of COVID-19 include an increase in the healthcare burden especially in the first months after the acute infection. The increased demand for resources can last up to two years after infection in particular subgroups of patients such as subjects admitted to hospital during the acute phase due to the severe presentation of the disease.